Crystallization and preliminary X-ray diffraction analysis of the lectin from Canavalia gladiata seeds - Moreno, FBMB; Delatorre, P.; Freitas, B. T.; Rocha, BAM; Souza, E. P.; Faco, F.; Canduri, F.; Cardoso, ALH; Freire, V. N.; Lima, J. L.; Sampaio, A. H.; Calvete, J. J.; et al. (Wiley-Blackwell, 2004)
The seed lectin from Canavalia gladiata was purified and crystallized. Orthorhombic crystals belonging to space group C222(1) grew within three weeks at 293 K using the hanging-drop vapour-diffusion method. Using synchrotron X-ray radiation, a complete structural data set was collected at 2.3 Angstrom resolution. The preliminary crystal structure of the lectin, determined by molecular replacement, had a correlation coefficient of 0.569 and an R factor of 0.412.